Penyuluhan Komprehensif dalam Islam untuk Membentengi Paham-Paham Radikalisme bagi Santri Pondok Pesantren - Mukh Nursikin; Budiyono Saputro; Edi Kuswanto (Yayasan Keluarga Guru Mandiri, 2022)
The notion of radicalism in religion is often considered a source of problems because it can damage and endanger the condition of the religious human system. The purpose of the activity is to conduct comprehensive counseling in Islam to fortify radicalism. The approach method used in this counseling is the lecture method and the question and answer method or discussion between extension participants and resource persons, and the counseling method carried out at the Annur Islamic Boarding School, Pabelan. The results of the activities obtained are the development and improvement of knowledge in Islam, attitudes and skills of students, ustadz and the community that have the ability to study, formulate, and have a sense of care to solve community problems based on an Islamic point of view. Integrating the role of universities, government, and society is an effort to maintain peace and tranquility and increase community participation in harmonious living together. The conclusion of this community service activity is to carry out this service activity which has an impact on improving the lives of religious communities and can minimize the understanding of radicalism in religion.